Advances in engineered Bacillus subtilis biofilms and spores, and their applications in bioremediation, biocatalysis, and biomaterials - Muhammad Zubair Mohsin; Rabia Omer; Jiaofang Huang; Ali Mohsin; Meijin Guo; Jiangchao Qian; Yingping Zhuang (Synthetic and Systems Biotechnology, 2021)
Bacillus subtilis is a commonly used commercial specie with broad applications in the fields of bioengineering and biotechnology. B. subtilis is capable of producing both biofilms and spores. Biofilms are matrix-encased multicellular communities that comprise various components including exopolysaccharides, proteins, extracellular DNA, and poly-γ-glutamic acid. These biofilms resist environmental conditions such as oxidative stress and hence have applications in bioremediation technologies. Furthermore, biofilms and spores can be engineered through biotechnological techniques for environmentally-friendly and safe production of bio-products such as enzymes. The ability to withstand with harsh conditions and producing spores makes Bacillus a suitable candidate for surface display technology. In recent years, the spores of such specie are widely used as it is generally regarded as safe to use. Advances in synthetic biology have enabled the reprogramming of biofilms to improve their functions and enhance the production of value-added products. Globally, there is increased interest in the production of engineered biosensors, biocatalysts, and biomaterials. The elastic modulus and gel properties of B. subtilis biofilms have been utilized to develop living materials. This review outlines the formation of B. subtilis biofilms and spores. Biotechnological engineering processes and their increasing application in bioremediation and biocatalysis, as well as the future directions of B. subtilis biofilm engineering, are discussed. Furthermore, the ability of B. subtilis biofilms and spores to fabricate functional living materials with self-regenerating, self-regulating and environmentally responsive characteristics has been summarized. This review aims to resume advances in biological engineering of B. subtilis biofilms and spores and their applications.